Audio fade profile customizing by imposing the audio volume initial rate of change - Lupsa-Tataru, Lucian (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
By adopting a rational function of degree 1, with the playback position in the course of an audio fade transition as the function input, and the audio volume as the function output, we advance a technique of setting up the audio fade profile by bringing forward a shape parameter that is directly proportional to the initial rate of change of the audio volume. We provide the relationships that are essential for computing the coefficients of the adopted rational function having at hand the audio effect characteristics, i.e. the fade length, initial volume, final volume and the parameter used for shaping. The versatility of the proposed technique is revealed by the numerous curves illustrating fade in, fade up, fade out and fade down transitions. The shape parameter is of key significance here having in view that it decides the pattern to follow. More precisely, one can set the value of the shape parameter in order to get either a fade effect that acts similar to the exponential shape fade or a fade effect that follows the pattern of the logarithmic shape fade. With a view to real time experimentation, a practical application, developed via plain JavaScript, is provided in the paper.